Comparative method to determine the geographic azimuth – geophisical obsevatory of Huancayo - Peru - Santos Rodríguez, Ricardo (2007)
The present study had as an specific objective to develop a methodology that, having a solid theoretical support, in the country of the Geodesic Astronomy, permits us to determine the orientation of an alignment with a minimum precision that serves as base for every project of engineering. For which after the bibliographical review specialized existing, the analysis was performed and evaluation of the results that permitted the approach in direct form of the determination of the direction of the azimuth geographical by different methods, in order to compare and to obtain a better solution in the determination of the azimuth, being utilized the following methods: By solar observations, making use of the theodolite of precision to the second, doing use of the conventional method and the clock angle. By observation to the stars, doing use of the theodolite with precision to the second, supported in the methods conventional and of the clock angle. By the gyroscope and by the system of global positioning (GPS). Being obtained with those methods precisions of to ±1.5”; nevertheless by means of the observations to the stars and under the method of the hourly angle, the precisions that are reached is of ±0.5”. For every work of order “C”, is sufficient and necessary the to obtain the direction of the meridian by observations to the Sun, being obtained a precision of ± 5”.